Use of Econometric Model in Forecasting Gross Regional Product - Usmanov Akramjon Ahmadjonovich (European Science Publishing, 2023)
This article focuses on the process of forecasting, which is one of the main directions of economic research. Definitions given by a number of economists to the terms forecast and forecasting were observed and personal opinions expressed by the author. In addition, the importance of econometric models in the process of forecasting is justified, and this is justified by the example of the object selected for research.
Keywords: Operational decision, econometric model, random events, trend, approximation, forecast, forecasting, tendency, analysis, correlation, regression, systematic analysis, induction, deduction, gross domestic product, time series.